(untitled) (Fiep Bulletin - online, 2013)
Knowing the level of physical performance of adolescents is critical for planning physical education classes, enabling the development of more effective practices that lead adolescents to develop physical fitness. The present study aims to evaluate aspects of health-related physical fitness of high school students, diagnosing delays in physical performance. The sample consisted of 58.5% of students in the 1st year of high school at a public school in the municipality of Jacareí, ie, 76 adolescents of both sexes with an average age of 15.16 years, 46 males and 30 females. All subjects had their fitness tests to evaluate the motors driven by Project Sport Brazil (PROESP). The data were discussed through descriptive analysis, measures of central tendency (mean) and dispersion (standard deviation) and compared between genders T test, with significance level p <0.05. The results indicated that the majority of normal subjects results obtained in tests Body Mass Index. For testing abdominal strength, flexibility, strength testing lower limb and upper, speed and agility boys showed significantly better results compared with girls, classified as reasonable and good. The girls were classified as reasonable and weak, indicating problems in physical performance. The questionnaire results showed that 85.92% of the subjects participating in class and that the activity most practiced team sport that year was 94.36% of classes being also observed that 59.15% engage in some kind of activity outside of school. You have to re plan the physical education classes, seeking to improve the level of fitness, especially for girls, and encourage them to seek physical activity, providing them with autonomy in choosing activities that can bring you better use the health promotion.